Staphylococcus aureus enterotoxin sensitization is associated with declined capsaicin cough sensitivity in chronic obstructive pulmonary disease - Yoshihiro Kanemitsu; Kensuke Fukumitsu; Ryota Kurokawa; Taisuke Akamatsu; Satoshi Fukuda; Yutaka Ito; Yuki Amakusa; Tatsuro Suzuki; Keima Ito; Yuta Mori; Takehiro Uemura; Tomoko Tajiri; et al. (Scientific Reports)
Abstract Sensitization to Staphylococcus aureus (S. aureus) enterotoxins (SEs) A (SEA) and B (SEB) is associated with the pathogenesis of several chronic airway diseases, including asthma and chronic rhinosinusitis, but its role in chronic obstructive pulmonary disease (COPD) remains unclear. This cohort study aimed to investigate the impact of sensitization to SEs on total IgE levels, and capsaicin cough reflex sensitivity (C-CS) in COPD. This study prospectively enrolled 68 patients with COPD from the outpatient department at Nagoya City University Hospital and Shizuoka General Hospital, Japan, from June 2018 to January 2020 for posthoc analysis. Patient characteristics and biomarkers, including total IgE, and C-CS, were collected. We additionally measured and serum SEA-IgE and SEB-IgE levels for this analysis. Total IgE and SEs-IgE levels in individuals with COPD were compared to those of 20 healthy individuals. The correlation between C-CS and IgE levels was evaluated using Pearson’s correlation coefficient. Multivariate analyses were used to adjust the impact on SE sensitization in total IgE levels and C-CS. The prevalence of SEs sensitization was higher in patients with COPD (23.5%, N = 16) than in healthy individuals (0%, N = 0) at a cut-off value of 0.35 UA/mL or more (p = 0.018). There was a negative correlation between total serum SEB-IgE levels and declined C-CS values. Multivariate analysis showed that SEs sensitization was associated with increased total IgE levels, and declined C-CS values. This study indicated that SEs sensitization was associated with increased IgE levels and decreased C-CS in COPD. This study was approved by the ethics committee of Nagoya City University (60-18-0012) and registered in the UMIN Clinical Trials Registry (Registry ID UMIN000032497).